THE CO-ORDINATION OF ACTIVITIES AND PERFORMANCE OF REHABILITATION PROJECTS FOR SOCIAL REINTEGRATION OF JUVENILE OFFENDERS IN KIRINYAGA COUNTY, KENYA - KIRUKI, HARRISON MWITI; Anthony Ndungu (IJRDO - Journal of Social Science and Humanities Research, 2021)
The purpose of this study was to assess the co-ordination of activities and performance of rehabilitation projects for social reintegration of juvenile offenders in Kirinyaga County, Kenya. The objective of this research article was to investigate the influence of learning activities co-ordination on performance of rehabilitation projects for social reintegration of juvenile offenders in in Kirinyaga County, Kenya, to investigate the influence of guidance and counselling activities coordination on performance of rehabilitation projects for social reintegration of juvenile offenders in Kirinyaga County, Kenya and to determine the influence of pre and post self-support activities coordination on performance of rehabilitation projects for social reintegration of juvenile offenders in Kirinyaga County, Kenya. Specifically, the study targeted 60 respondents (Institution staff, probation officers and children officers) respectively, responsible for the day to day operations in the departments responsible for the efficiency of rehabilitation projects for social reintegration of the juvenile offenders in the region. Data collected in this study was analysed via quantitative approach and assembled to form the final findings and interpretations. The study adopted all variables with a Cronbach Alpha of above 0.7. The study concluded out that; majority of the staff were in agreement that; they were happy that coordination of activities in the enhancement of rehabilitation projects outcomes for social reintegration of juvenile offenders has been efficient, there has been inadequate coordination by state and government officials which might be a root factor on the efficiency running of rehabilitation centers, there is poor coordination among departments, agencies and ministries in the Juvenile Justice System (JJS), the department of probation and aftercare services, department of children’s services and policy-makers are always mindful that rehabilitation efforts do not appear inconsistent or unfair in any way and that they are happy that collaboration and communication between service providers has been able to help the JJS especially on social reintegration. The study recommends that the management continue with the motive of ensuring that all activities related to co-ordination are well put into records and followed to the latter to enhance efficiency of rehabilitation projects for social reintegration of the juvenile offenders in Kirinyaga County, Kenya. Critical assessments must be done always to find out the issues related coordination in order to ensure that the challenge is addressed especially in the areas concerned such as communication, task allocation, task management and in related records management. The researcher recommends that the government and the affiliated institutions as well as the management in place acting in various capacities remain focused towards counteracting challenges related to coordination of learning, guidance and counselling and pre and post support activities that influence the performance the rehabilitation projects for social reintegration of the juvenile offenders in Kirinyaga County, Kenya. The study recommends that the government streamlines policies and guidelines to promote coordination of activities through collaboration and networking within the juvenile justice system as well as in the agencies so as to enhance effectiveness in rehabilitation and social reintegration of juvenile offenders in Kirinyaga County, Kenya.